PELATIHAN AKUNTANSI DASAR UNTUK MENGEMBANGKAN HARD SKILL SISWA SMK - Bambang Tutuko; Abdul Latif (Politeknik Negeri Sriwijaya, 2022)
Vocational High School (SMK) students experience problems in learning and developing basic accounting knowledge along with understanding accounting concepts recently affected by the International Financial Reporting Standard (IFRS). There needs to be an understanding of financial statements that can be obtained through basic accounting training to improve basic accounting scientific abilities. Basic accounting training to improve students' hard skills can make it easier for students to upgrade their ability to analyze financial report data. This training at SMKN 25 provides basic accounting concepts so that students have a solid description and foundation to minimize the error rate of prospective accountants. Furthermore, this training activity aims to develop students' hard skills so that they can easily understand and apply basic accounting. Introduction and development of accounting knowledge through basic accounting training are needed to produce competent and credible accounting graduates.